Find all solutions of (x/x-3) + (x^2+2/x^2-9) = 2x/x+3
(and the answer is supposed to be in a fraction)
x/(x-3) * (x+3) / (x+3) + (x^2+2)/(x^2-9) = 2x / (x+3) * (x -3) / (x-3)
(x^2 + 3x + x^2 +2) / (x^2 -9) = (2x^2 - 6x) / (x^2 -9)
Multiply entire equation by (x^2 -9)
2x^2 + 3x + 2 = 2x^2 - 6x
9x + 2 = 0
9x = 2
x = 2/9
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?